OP0008 Peripheral Blood B Cell Subsets and BAFF/April Receptor Expression, Together with Circulating BAFF and April Levels, are Disturbed in Rheumatoid Arthritis but not in Ankylosing Spondylitis. (23rd January 2014) - Gaugler, B.; Laheurte, C.; Bertolini, E.; Wendling, D.; Saas, P.; Toussirot, E.
Abstract : Background: B cells play a critical role in systemic autoimmune disease and especially rheumatoid arthritis (RA). BAFF and APRIL are involved in B cell activation and survival. Few studies have evaluated the distribution of the different peripheral blood B cell subsets in RA as well as the expression of BAFF/APRIL receptors. Ankylosing spondylitis (AS) is an inflammatory rheumatic disease without current evident contribution of B cells to the inflammatory response. Objectives: to evaluate the distribution of circulating B cell subsets and the expression of BAFF/APRIL receptors (TACI, BCMA and BAFF-R) as well as the circulating levels of BAFF and APRIL in patients with RA or AS compared to healthy controls (HC). Methods: 59 patients with RA (ACR criteria, 12 M, age [mean ±SEM; years]: 58 ± 1.5, disease duration : 10.1 ± 1.5; all under traditional DMARDs, no biologics, corticosteroids < 10 mg/day N= 33), 61 patients with AS (modified NY criteria; 46 M; age : 46 ± 1.8, disease duration:11.6 ± 1.2; all under NSAIDs or traditional DMARDs) and 61 HC (13 M; age: 43.6 ± 1.8) were evaluated. For each subject, peripheral blood B cell subsets were assessed using multi-color flow cytometry. B cell subsets were analysed according CD27, CD38 and IgD staining (naive B cells: CD27- IgD+ CD38lo, transitional: CD27- IgDlo CD38hi, pre-GC: CD27+IgD+CD38hi, post-GC: CD27+IgD-CD38lo). The expression of BAFF-BR3, TACI and BCMA was analysed on each subset. RFI was calculated by dividing the MFI of the marker divided by MFI of the isotype-matched mAb. BAFF and APRIL serum levels were determined by ELISA using commercially available kits (Bender MedSystems and R&DSystems) respectively. Results: Circulating BAFF and APRIL levels were increased in RA compared to HC (1100.5 ± 62.5 vs 904.9 ± 29.4 pg/ml, p= 0.01 and 19116.3 ± 4918.6 vs 5699.2 ± 1034.5 pg/ml, p < 0.001, respectively), while no difference was observed in the levels of these activating B-cell factors in AS and HC. The ratio BAFF levels/peripheral B cell count was also significantly increased in RA (p = 0.04). The following B cell subsets were decreased in RA compared to HC: total B cells (p= 0.004), naïve B cells (p = 0.02), transitional B cells (p < 0.001), while post GC and CD27+ B cells were not different. B-cell subsets were comparable in AS and HC. Expression of BAFF and APRIL receptors were increased in the RA group, especially TACI on CD19+ B cells, transitional B cells and pre GC B-cells (all p < 0.05) and BCMA on CD19+, naive B cells, transitional B cells, memory B cells, pre-GC and post-GC B-cells (p < 0.05) while BAFF-R RFI was comparable in RA and HC. The expression of BAFF/APRIL receptors did not differ between AS and HC. Conclusions: Overall, our data confirm that B cell responses are altered in RA with biased repartition of B cell subsets, elevated levels of B cell activating cytokines and increased expression of their receptors. These results may be helpful for guiding and /or monitoring B cell targeted therapies in RA. In contrast, no alteration was observed in AS patients excluding an involvement of disturbed B cell responses in AS. Disclosure of Interest: None Declared